Identification of Genomic Databases and Bioinformatics Analysis of Gene Variations in Behçet Syndrome Across Continental Populations - Dwiki Fitri; Husnul Khuluq; Diah Kurniasih; Muhammad Ma'ruf (Indonesian Journal of Global Health Research, 2026)
Behçet's Syndrome is a rare multisystem inflammatory disorder with an etiology that is not yet fully understood. The disease is characterized by various clinical manifestations, including recurrent oral and genital ulcers, ocular lesions, skin abnormalities, arthritis, central nervous system involvement, and vascular complications. Understanding the genetic factors associated with Behçet's Syndrome across different populations may provide insights into its pathogenesis and potential therapeutic targets. This study aims to identify genetic variations associated with Behçet's Syndrome across populations from different continents using a bioinformatics approach. Data were analyzed from the GWAS Catalog, HaploReg v4.2, GTEx Portal, and Ensembl Genome. Single nucleotide polymorphisms (SNPs) associated with Behçet's Syndrome were identified, and their tissue-specific gene expression and allele frequency across populations were investigated. Two main SNPs, rs17482078 and rs2617170, were identified as missense mutations in the ERAP1 and KLRC4 genes, respectively, both of which have been linked to various autoimmune diseases. GTEx Portal analysis revealed that ERAP1 is expressed in 30 tissues, including skeletal muscle, blood, brain regions (putamen, caudate, hypothalamus), skin, pancreas, esophagus, and other organs. KLRC4 expression was observed in 18 tissues, including the cerebral cortex, lungs, heart, small intestine, thyroid, prostate, and additional tissues. Ensembl Genome data indicated population-specific allele frequency variation: rs17482078 in ERAP1 was highest in Africa (94.6%), followed by East Asia (94.2%), South Asia (93.5%), the Americas (88%), and Europe (78%). SNP rs2617170 showed the highest frequency in Africa (57%), followed by South Asia (46%), East Asia (45%), Europe (34%), and the Americas (33%). The findings highlight ERAP1 and KLRC4 as key genetic factors associated with Behçet's Syndrome and demonstrate population-specific allele frequency differences. These results provide valuable insights into the genetic architecture of the disease and may guide future studies on its pathogenesis and potential therapeutic strategies.